End of legacy in the fishing business - Mumbai Archive Project Team (Jio Institute, 2024)
After her father’s demise, Saraswati’s brother, Om Prakash Nakhva, did not continue her father’s legacy in the fishing business. Instead, he made his career in the service industry, working at the Colaba docks. He married Meena, who now lives with Saraswati.